2017
DOI: 10.1007/s00246-017-1649-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analyses of a Novel CITED2 Nonsynonymous Mutation in Chinese Tibetan Patients with Congenital Heart Disease

Abstract: CITED2 gene is an important cardiac transcription factor that plays a fundamental role in the formation and development of embryonic cardiovascular. Previous studies have showed that knock-out of CITED2 in mice might result in various cardiac malformations. However, the mechanisms of CITED2 mutation on congenital heart disease (CHD) in Chinese Tibetan population are still poorly understood. In the present study, 187 unrelated Tibetan patients with CHD and 200 unrelated Tibetan healthy controls were screened fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Non-synonymous and synonymous variants in CITED2 sequence or reduced expression of CITED2 have been associated with CHD worldwide [25,26,39,[147][148][149][150]. Ventricular (VSD) and atrial (ASD) septal defects, transposition of the great arteries (TGA) and the tetralogy of Fallot (TOF) are the most frequent heart anomalies associated with CITED2 variants Regenerative Medicine Frontiers…”
Section: Cited Congenital Heart Disease and Adult Heart Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-synonymous and synonymous variants in CITED2 sequence or reduced expression of CITED2 have been associated with CHD worldwide [25,26,39,[147][148][149][150]. Ventricular (VSD) and atrial (ASD) septal defects, transposition of the great arteries (TGA) and the tetralogy of Fallot (TOF) are the most frequent heart anomalies associated with CITED2 variants Regenerative Medicine Frontiers…”
Section: Cited Congenital Heart Disease and Adult Heart Functionmentioning
confidence: 99%
“…https://doi.org/10.20900/rmf20190005 ( Figure 3). Most of CITED2 variants identified in patients with CHD, only marginally affect its capacity to repress the transcriptional activity of HIF-1ɑ and/or to co-activate TFAP2 ex vivo [25,26,39,[147][148][149][150]. However, CITED2 mutations in patients may result in severe impairment of VEGF and PITX2C gene expression, which are necessary for normal development of the vasculature and left-right patterning, respectively [26].…”
Section: Of 27mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that CITED2 prevents the activation of pro-angiogenic genes such as VEGF and inhibits angiogenesis by competing with HIF-1α to bind to CBP/P300 [32][33][34]. CITED2 is also known to act as a negative regulator of fracture healing, and its expression is inversely related to the expression of VEGF and HIF-1α genes [35][36][37][38]. The expression of CITED2 is up-regulated in vascular endothelial cells of diabetic patients, while over-expressed CITED2 inhibits transcriptional activation of HIF-1α and ultimately leads to angiogenesis disorders [39].…”
Section: Introductionmentioning
confidence: 99%
“…Knock-out experiments of CITED2 in mice may result in several cardiac defects. In a study involving 187 unrelated Tibetans with CHD, Liu et al found a novel mutation of CITED2 that enhanced the expression of vascular endothelial growth factor (VEGF) under the role of co-receptor hypoxia-inducible factor 1 alpha (HIF-1α) [10]. In this journal, in a recent issue, Pan et al studied the endothelial PAS domain-containing gene 1 (EPAS1) in CHD in Tibetans [11].…”
mentioning
confidence: 99%